Xanthan gum inhibits cartilage degradation by down-regulating matrix metalloproteinase-1 and -3 expressions in experimental osteoarthritis. (March 2014) - Han, Guan-Ying; Mei, Xi-Fan; Ling, Pei-Xue; Guo, Yue-Wei; Zhu, Xi-Qiang; Shao, Hua-Rong; Liu, Fei; Zhang, Tian-Min
We previously reported that intra-articular injection of xanthan gum protected the joint cartilage and reduced osteoarthritis progression. In this study, the effects of xanthan gum on chondrocytes apoptosis were evaluated using the labeling assay, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling assay, to determine the protein expression of matrix metalloproteinase-1, 3, and tissue inhibitors of metalloproteinase-1 using immunohistochemistry and Western blot assay in cartilage of papain-induced rabbit osteoarthritis model. Compared to the negative control group, intra-articular injection of xanthan gum, once every 2 weeks for 5 weeks significantly inhibited chondrocytes apoptosis and matrix metalloproteinase-1 and -3 protein expression levels and also enhanced the tissue inhibitors of metalloproteinase-1 production in cartilage. No significant differences between the xanthan gum-treated group and the sodium hyaluronate-treated group (intra-articular injection of sodium hyaluronate only once a week for 5 weeks) were observed.